(untitled) (Research, Society and Development, 2022)
It is estimated that the world population will be close to 9 billion in 2040. Compared to consumption in 2010, Attendance this demand will require a further increase, accounting for more than 35% of total energy supply. This will require more diversified energy resources. The use of floating photovoltaic systems has progressed in many countries, as it is a new strategy, there are still few studies on these systems. Among the advantages of using these devices stand out improved conversion efficiency, the reduction of evaporation from the water surface and reduction of algae growth. In this sense, this study aimed to carry out a literature review on the main obstacles and challenges of implementation in Brazil. Databases in the area of environmental sciences and engineering were used, such as: Academic Google, Scientific Electronic Library Online (SciELO) and CAPES Journal Portal. In this review, it was possible to observe that the energy sector has been adapting according to its energy crisis processes, where new production alternatives tend to supply a large portion of the population. It is of paramount importance both in preventing blackouts and in the perspective of having a hybrid system. Another important data found that, each location had its particularity, but the main obstacles and challenges are the economic viability in the detriment of systems made on the ground and attendence of all the current technical and safety requirements necessary for its installation and operation.